The Home Carrier Advantage in Civil Aviation - Mark Lijesen; Peter Nijkamp; Eric Pels (Tinbergen Institute, 2005)
This paper analyzes the relative economic power position of home carriers in hub-and-spoke systems. Hub-and-spoke systems may lower costs on densely traveled routes and enable economically viable operations on less densely traveled routes. The reverse side is probably that carriers enjoy significant market power at their home base, often labeled the home carrier advantage. The paper offers a concise overview of the literature in this field, and addresses next empirically this issue for European home carriers. We found empirically that at least some European carriers charge premiums for flights originating from their hubs. The hub premiums of Lufthansa, Swissair and Air France are significantly higher than those of the other companies in our sample.
Keywords: R41; D4; 330; Airlines; airports; networks; homecarrier advantage; Luftverkehr; Hub-and-Spoke-Netzwerk; Netzwerkökonomik